Perkembangan dan Keminatan Perbankan Syariah dan Perbankan Konvensional Terhadap Transaksi Keuangan - Yusman Yusman (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Bank is a business entity whose main task is as a financial intermediary, which distributes funds from parties who have excess funds to parties who lack funds, at a specified time. Bank is a business entity engaged in finance or financial services. A commercial bank is one of the financial institutions that has a very important role as a driver of the economic life of every free country (free economy). A bank based on sharia principles is a rule of agreement based on Islamic law between a bank and other parties to save funds or finance business or other banking activities. However, abroad, especially in Middle Eastern countries, banks based on sharia principles have been growing rapidly for a long time. Empirical juridical research method, data analysis used in a qualitative normative way with reinforcement on field data. The results of the study show the development of public confidence in the interest of financial transactions and regulations relating to banking problems in Indonesia regulated in Law no. 7 of 1992 concerning Banking as amended by Law no. 10 of 1998. Based on Article 1 number (2) of Law no. 10 of 1998, and the development of banking that is more accommodating and provides opportunities for the development of Islamic banking, with the presence of Law Number 21 of 2008, concerning Islamic BankingKeywords: Public Trust; Interest; Financial Transactions AbstrakBank merupakan badan usaha yang tugas utamanya sebagai lembaga perantara keuangan (financial intermediaries), yang menyalurkan dana dari pihak yang kelebihan dana kepada pihak yang kekurangan dana, pada waktu yang ditentukan. Bank merupakan suatu badan usaha yang bergerak di bidang keuangan atau jasa keuangan. Bank komersial adalah salah satu institusi finansial (finansial institution) yang sangat penting perananya sebagai penggerak kehidupan ekonomi setiap negara bebas (free economy). Bank berdasarkan prinsif syariah adalah aturan perjanjian berdasarkan hukum Islam antara bank dengan pihak lain untuk menyimpan dana atau pembiayaan usaha atau kegiatan perbankan lainya. Namun, di luar negeri terutama di negara-negara timur tengah bank yang berdasarkan prinsif syariah sudah berkembang pesat sejak lama. Metode Penelitian yuridis emperis, analisa data yang digunakan dengan cara normatif kualitatif dengan penguatan pada data lapangan. Hasil penelitian menunjukan perkembangan keminatan kepercayaan masyarakat, terhadap transaksi keuangan dan Pengaturan yang berkaitan dengan masalah bank di Indonesia diatur dalam Undang-Undang No. 7 Tahun 1992 tentang Perbankan sebagaimana telah diubah dengan Undang-Undang No. 10 Tahun 1998. Berdasarkan Pasal 1 angka (2) Undang-Undang No. 10 Tahun 1998, dan perkembangan Perbankan yang lebih mengakomodasi dan memberi peluang bagi perkembangan perbankan syariah, dengan kehadiran undang-undang Nomor 21 tahun 2008, tentang Perbankan SyariahKata Kunci: Keminatan kepercayaan; Masyarakat; Transaksi Keuangan